Triple Regimen with Rituximab, Plasmapheresis and Intravenous Immunoglobulin in the Treatment of Dialysis Dependent Acute Humoral-Mediated Rejection in Kidney Grafts - Pessegueiro, P (2006)
Introduction: The clinical importance of humoral-mediated acute rejection has been progressively recognised. Early recognition and treatment with plasmapheresis and intravenous immunoglobulin have recently improved short term prognosis. Case report: In this report we describe the clinical features of three 2nd transplant patients developing severe acute humoral rejection during the first week post-transplant while on anti-thymocyte globulin therapy. Treatment with plasmapheresis/ intravenous immunoglobulin/rituximab resulted in rapid reversal of oliguria,and recovery of renal function within the 1st week of treatment in 2/3 patients. Diagnosis was confirmed by graft biopsies revealing peritubular neutrophiles and C4d deposits. Sequential graft biopsies in all three patients revealed complete histological recovery within two weeks. One patient never recovered renal function, and one patient lost his graft at three months following hemorrhagic shock. After 2 years follow up, the remaining patient maintains a serum creatinine of 1.1mg/dl. Conclusion: The regimen using plasmapheresis plus intravenous immunoglobulin and rituximab was effective in rapidly reversing severe acute humoral rejection.